2019
DOI: 10.1088/1361-6455/ab165c
|View full text |Cite
|
Sign up to set email alerts
|

Interferences in the photoionization of water molecules

Abstract: We study theoretically the photoionization of water molecules by monochromatic and linearly polarized radiation. The final state wavefunctions are given by coulomb continuum wavefunctions and the water molecule bound states are represented using linear combinations of Slater-type orbitals located on the centers of the molecule. We obtain total and differential cross sections. We compare them with more elaborated theoretical results and experiments obtaining a very good agreement in particular at enough high en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…If the coherences between the centers are accounted for (as done, e.g., in Refs. 82,83), the multi-center treatment should be able to smoothly cover both short-distance and long-distance cases (or, equivalently, low-energy and high energy regimes). In the current implementation in ezDyson, the coherences are neglected, so that the multi-center model is only appropriate for high-energy regime, when the de Broglie wavelength of photoelectrons is shorter than the distance between the centers.…”
Section: Single-center Versus Multi-center Treatment Of the Photoelec...mentioning
confidence: 99%
“…If the coherences between the centers are accounted for (as done, e.g., in Refs. 82,83), the multi-center treatment should be able to smoothly cover both short-distance and long-distance cases (or, equivalently, low-energy and high energy regimes). In the current implementation in ezDyson, the coherences are neglected, so that the multi-center model is only appropriate for high-energy regime, when the de Broglie wavelength of photoelectrons is shorter than the distance between the centers.…”
Section: Single-center Versus Multi-center Treatment Of the Photoelec...mentioning
confidence: 99%
“…The CC wavefunction takes into account the Coulomb interaction of the electron with the residual target in the final channel of the reaction. It has been shown that this interaction must be included to describe the photoionization reaction with neutral targets in the correct manner [20][21][22][23][24].…”
Section: Second-order Time-dependent Perturbation Theorymentioning
confidence: 99%
“…Although the outgoing electron experiences asymptotically a +1 charge, the Coulomb potential in the vicinity of the target is different due to the screening of the polyatomic nuclear potential by the remaining electrons. The effect of the screening can be accounted for by using effective charges ,, and a multicenter expansion. , Figure shows the results computed with a plane-wave approach ( Z = 0) and with physically motivated effective charges, Z eff computed by Belkić’s rule, based on the generalization of the Rydberg formula for the energy levels of a hydrogen-like atom (Figure S9 in the Supporting Information shows the results with other values of Z eff ).…”
mentioning
confidence: 99%
“…The transition between the two regimes depends on the photoelectron energy, which determines de Broglie’s wavelength (λ) of the photoelectron: if the distance between the two centers ( R ) is larger than λ, then one can treat the photodetachment as two independent noninterfering waves, whereas for λ ∼ R , the two waves interfere, and the photodetachment signal reveals an entangled state. One can arrive to this intuitive result formally by analyzing the effect of coherences between the two centers using the multicenter treatment of photoionization , (the derivation is given in the Supporting Information). The mathematical reason that the coherences are diminished at high energy is rooted in the oscillatory behavior of the phase between the two waves: the frequency of the oscillations equals , where E is the energy of the photoelectrons.…”
mentioning
confidence: 99%